Meta-Analysis of Bioprosthetic Valve Thrombosis After Transcatheter Aortic Valve Implantation - Rheude, Tobias; Pellegrini, Costanza; Stortecky, Stefan; Xhepa, Erion; Ammon, Fabian; Pilgrim, Thomas; Mayr, N. Patrick; Husser, Oliver; Achenbach, Stephan; Windecker, Stephan; Cassese, Salvatore; Joner, Michael; et al. (American Journal of Cardiology, 2020)
Bioprosthetic valve thrombosis may complicate transcatheter aortic valve implantation (TAVI). This meta-analysis sought to evaluate the prevalence and clinical impact of subclinical leaflet thrombosis (SLT) and clinical valve thrombosis (CVT) after TAVI. We summarized diagnostic strategies, prevalence of SLT and/or CVT and estimated their impact on the risk of all-cause death and stroke. Twenty studies with 12,128 patients were included. The prevalence of SLT and CVT was 15.1% and 1.2%, respectively. The risk of all-cause death was not significantly different between patients with SLT (relative risk [RR] 0.77; p = 0.22) and CVT (RR 1.29; p = 0.68) compared with patients without. The risk of stroke was higher in patients with CVT (RR 7.51; p <0.001) as compared with patients without, while patients with SLT showed no significant increase in the risk of stroke (RR 1.81; p = 0.17). Reduced left ventricular function was associated with increased prevalence, while oral anticoagulation was associated with reduced prevalence of bioprosthetic valve thrombosis. Bioprosthetic valve thrombosis is frequent after TAVI, but does not increase the risk of death. Clinical valve thrombosis is associated with a significantly increased risk of stroke. Future studies should focus on prevention and treatment of bioprosthetic valve thrombosis.
CRIS-Team Scopus Importer:2020-11-06